Bioethanol Production from Ulva lactuca Macroalgae: Optimation of Acid Hydrolysis and Fermentation Time - Assyifa Junitasari; Satiyarti, Rina Budi; RR. Nadya Shafa Afrida; Asep Supriadin (ORGANISMS: JOURNAL OF BIOSCIENCES, 2026)
Nowadays bioethanol has been developed as a new renewable energy source of fuel because it has the same characteristics as ethanol, can increase the octane number in gasoline and be able to reduce CO2 emissions significantly. Bioethanol based on a natural ingredient of macroalgae can be used as fuel because it contains carbohydrates of glucose that can be fermented into alcohol through the process of acid hydrolysis. The study aims to identify the optimal fermentation time  and analyze the levels of bioethanol produced using GC-MS instruments from Ulva lactuca macroalgae type. The production of bioethanol was carried out using the acid hydrolysis method with H2SO4. The reducing sugar content was analyzed using the Luff-Schoorl method, followed by fermentation using Saccharomyces cerevisiae. Acid hydrolysis was conducted using 2 N H2SO4 at 80ºC for 120 minutes. Fermentation time was varied into three treatments, namely 72, 96, and 120 hours. Each treatment was performed in triplicate. The observed parameters included reducing sugar content, ethanol concentration, and bioethanol yield. Data obtained from the experiment were analyzed descriptively and presented as mean values to evaluate the effect of fermentation time on bioethanol production efficiency. The results of this study produced 15,72% reducing sugar and 0,9% bioethanol content. Accordingly, the best times of fermentation to produce bioethanol from Ulva lactuca macroalgae is for 72 hours